Ethnicity in Special Education A Macro-level Analysis. A Project ALIGN Issue Brief - Virginia Commonwealth Univ., Richmond. Commonwealth Inst. for Child and Family Studies; Mitchell, Melissa; Virginia Commonwealth Univ., Richmond. Commonwealth Inst. for Child and Family Studies ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This policy brief examines the role of ethnicity in special education by reporting on a study of the impact of base rates of ethnicity on the identification, placement, and graduation rates of children with disabilities. Emphasis is on system characteristics rather than individual student characteristics. The study explored the relationship between the percentage of non-white students in states' school populations and the rates at which special education students are identified, placed in restrictive settings, and graduate from school. States' data were obtained from the National Center for Educational Statistics. Regarding identification, the correlation between percentage of white and the identification rate was quite low, suggesting ethnicity was not related to rate of identification as disabled. As far as placement, the study found that ethnicity was a statistically significant predictor of placement in regular class settings. With regard to graduation, the study examined the relationship of ethnicity to graduation by diploma, by certificate, and by both diploma and certificate. Ethnicity was not significantly related to graduation by diploma or diploma and certificate combined, but was moderately correlated with graduation by certificate. Scattergraphs and tables detail the study's findings. (DB)
Availability: Donald Oswald, Commonwealth Institute for Child and Family Studies, Dept. of Psychiatry, MCV/VCU, P.O. Box 980489, Richmond, VA 23298-0489.
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: H023A50114.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Degrees (Academic); Disabilities; Disability Identification; Elementary Secondary Education; Ethnic Groups; Ethnicity; Graduation; Mainstreaming; Minority Groups; Racial Factors; Special Education; Statistical Analysis; Student Placement; Graduation Rates; Information Analyses; Reports, Evaluative